HERMENEUTIKA MUHAMMAD TALBI: Diskursus pemimpin non muslim dalam Konteks Indonesia - Abd. Rahman (STAI Darul Kamal NW Kembang Kerang, 2020)
Talbi, one of the Muslim intellectuals who has a special attention to modern and interreligious issues, has offered a new theory of interpreting the Quran, namely Qiraat Tarikhiyyah (Historical Reading), a theory built from the statement that a Muslim historian when dealing with religious texts, will forever be based on Qiraat Unasiyah (Humanistic reading). The main principle built into this theory is the Maqashid principle (Muqarabah Maqashidiyah). This article will explore more about how Qiraat Tarikhiyyah works in an effort to understand and interpret the Quran. By using a historical approach and a humanistic perspective, the theory offered by Talbi will be tasted for its relevance in the context of interpreting verses about non muslim leaders, especially in Indonesian context.